Comparison of Indigenous Microbial Flora of the Eye to that Found in Conjunctival and Corneal Infections in A Hospital Based Study - Wajid Ali Khan, Shehla Rubab, Haroon Awan (Pakistan Journal of Ophthalmology, 2006)
Purpose: To determine the normal indigenous microbial flora and to compare it with pathogens, which cause conjunctivitis and keratitis. Material and Methods: A case-control prospective hospital based study was done. The control group (350 persons) included patients waiting for cataract surgery, hospital personnel, visitors and accompanying persons, while the cases group (150 persons) comprised of individuals with bacterial conjunctivitis, fungal and bacterial keratitis. Gram and Giemsa staining was performed on all specimens from conjunctival swabs and corneal scrapings. Blood, chocolate and Sabouraud’s agars were used to grow the bacteria and fungi. Sensitivity of yielded bacteria was checked against antibiotics using standard sensitivity discs. Results: The study demonsrtated a male preponderance in both groups. Common organisms found in the control group were Staph. epidermidis, Staph. aureus, Strep. pneumoniae and Diptheroides spp, while those found as pathogens were Staph. aureus, Strep. pneumoniae, Staph. epidermidis and Strep. pyogenes in the conjunctivitis group and Strep. pneumoniae, Staph. aureus, Hemophilus spp. and Pseudomonas in the keratitis group. In the cases group, over 80% of Staph. aureus showed sensitivity against gentamicin, chloramphenicol and cephradin. About 80% of pneumococci were sensitive to chloramphenicol, cephradin and erythromycin. The presence of Staph. epidermidis in the control group was highly significant (p<0.000). Staph. aureus did not show any significant difference in the either groups. Strep. pneumoniae, Staph. pyogenes, Pseudomonas and fungi had a significantly higher prevalence in the keratitis and conjunctivitis groups. Conclusions: Gentamicin and chloramphenicol are still an effective and economical first line treatment for most cases of conjunctivitis and keratitis. Key Words: Ocular commensals, Ocular opportunistic pathogens, Microbial flora of the eye, Conjunctivitis, Keratitis, Eye infections.